Impact of bulk deposition of anions as diffuse source in preto river, são paulo state, Brazil - Martins, F. C.S. [UNESP]; Medeiros, F. H. [UNESP]; Valerio, S. R. [UNESP]; Moreira, A. B. [UNESP]; Bisinoti, M. C. [UNESP] (My University, 2010)
Bulk and wet depositions were measured during two hydrological years (January, 2(308 to January, 2010) in the Sao Jose do Rio Preto city. Water samples of total and wet depositions were collect from the Preto river after each rain and the pa rameters pH, conductivity, nitrate, ammonium, phosphate, total organic carbon and sulphate were quantified following official method recommendations. The amounts of each previously mentioned compound in the total deposition from the Preto river were determined. The principal aquatic body of the city is this river which supplies 30-40% of its water for approximately 417.000 inhabitants. Average total deposition from 160 rains of TOC, NH3, NO3-, SO42- and PO43- was 34.5; 3.45; 2.72; 25.2 and 1.92 mg m-2day-1. If we presume that the atmospheric deposition is all cast into the Sao Jose do Rio Preto (SJRP) municipal reservoir, which is of 402.000 m2 and 2 m deep, this would represent a COT of 2.6%, as well as 2.7%, 0.5%, 0.4% and 10% of all NO3-, NO3-, SO42- and PO43-present in this aquatic body. It can be concluded that SJRP has an atmospheric deposition comparable to that of large urban centers. Moreover, the amount of pollutants from total deposition in said reservoir is equivalent to 10% of the phosphorus parameter and inferior to 3% for the rest, which places the total deposition as a significant diffused source of pollution. No. 037.